Changement climatique. Sur les cartes et les narrations - Elena Bougleux (Archivio Antropologico Mediterraneo)
The strategies for adaptation and resilience to climate change challenge the ongoing distinctions between the natural and the cultural. These coupled and inseparable concepts become fully interdependent in specific conditions of environmental change, when traditional representations of space and environment become inadequate to describe swiftly occurring transformations. Mapping techniques have made progresses at the local level but they need to include knowledge and approaches inherited from the past to develop new kind of adaptive information patterns. The paper describes examples of spatial change representations developed by Aboriginal communities who live in strict coupling with their natural environment. It focuses on the area of the Northern Territory of Australia which faces a condition of long-lasting coexistence with altered tides regimes and massive land degradation due to large wildfires. The orientation system adopted by Aboriginal communities over the land and by the sea has changed to include GIS technologies, developing a hybrid techno/visual language which allow both the space and the people to be represented by visual means, narrations and technical data.